Complete Genome Sequences of Two Swiss Hepatitis E Virus Isolates from Human Stool and Raw Pork Sausage - Kubacki, Jakub; Fraefel, Cornel; Jermini, Marco; Giannini, Petra; Martinetti, Gladys; Ripellino, Paolo; Bernasconi, Enos; Sidler, Xaver; Stephan, Roger; Bachofen, Claudia (Genome announcements (Washington, DC), 2017)
We present here the full-length genome sequences of two hepatitis E virus genotype 3 (HEV-3) isolates from a human stool sample from a patient with acute hepatitis and a raw sausage containing pig liver. Sequence analysis implies that Swiss HEV isolates may form a novel subgroup of HEV-3 viruses.